Rancang Bangun Sistem Informasi Manajemen Penyewaan Lapangan Futsal "ZUPER" - mufadilah, lani; amrozi, yusuf (INTEGER: Journal of Information Technology, 2019)
Zuper futsal field rental is a business entity engaged in the field of rental services that require the existence of an information system. Information systems in a company play an important role in the progress and management of a company as well as in the zuper rental system that is to be able to support and provide satisfactory services to each customer. The system that exists in some futsal fields in general is still simple with menual management, most of the problems that are often encountered are the process of recording data and transactions requiring a long time. The possibility of errors in writing a data and the security of the document is not guaranteed, because many lost documents will make it difficult for you to do a data search or report printing. Designing an application in the form of a program that functions to process and simplify business processes that occur on the Zuper futsal field, starting from the data processing of tenants, leasing transactions, to printing reports are expected to be the best solution to solve problems that exist in a business entity to support efficiency and the effectiveness of working on a field rental